Financial Crime In The Perspective of Criminal Law - Rumangun, Johan., Pieter., Elia; Borolla, Luciana (Journal of Economics, Business, and Government Challenges, 2022)
This study aims to analyst the Financial Crime in the Perspective of Criminal Law. This study used a survey method and Employees at the Regional Government of the Aru Islands District as the research subject. Data collection techniques used were interview and observations techniques. The data obtained were analysed using qualitative descriptive analysis techniques. The results of this research is that financial crimes often occur within the scope of local government. This is due to a weak internal control system from the leadership on employee performance.